An Error-Related Negativity Potential Investigation of Response Monitoring Function in Individuals with Internet Addiction Disorder - Zhou, Zhenhe; li, cui; zhu, hongmei (Frontiers in Behavioral Neuroscience, 2013)
Internet addiction disorder (IAD) is an impulse disorder or at least related to impulse control disorder. Deficits in executive functioning, including response monitoring, have been proposed as a hallmark feature of impulse control disorders. The error-related negativity (ERN) reflects individual’s ability to monitor behavior. Since IAD belongs to a compulsive-impulsive spectrum disorder, theoretically, it should present response monitoring functional deficit characteristics of some disorders, such as substance dependence, ADHD or alcohol abuse, testing with an Erikson flanker task. Up to now, no studies on response monitoring functional deficit in IAD were reported. The purpose of the present study was to examine whether IAD displays response monitoring functional deficit characteristics in a modified Erikson flanker task. 23 subjects were recruited as IAD group. 23 matched age, gender and education healthy persons were recruited as control group. All participants completed the modified Erikson flanker task while measured with event-related potentials (ERPs). IAD group made more total error rates than did controls (P < 0.01); Reactive times for total error responses in IAD group were shorter than did controls (P < 0.01). The mean ERN amplitudes of total error response conditions at frontal electrode sites and at central electrode sites of IAD group were reduced compared with control group (all P < 0.01). These results revealed that IAD displays response monitoring functional deficit characteristics and shares ERN characteristics of compulsive-impulsive spectrum disorder.